(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the clinical effects of miswak and tooth brushing on gingivitis at Isra University Hospital Hyderabad Study Design: observational study Place and Duration of Study: This study was conducted at the patients visiting Periodontology Department Isra University Dental College and Hospital from July 2018 to January 2019. Materials and Methods: This observational study was conducted in patients visiting Periodontology Department Isra University Dental College and Hospital from July 2018 to January 2019. The selection of the patients was assigned to group A (n=30) who used tooth brush and group B (n=30) who used Miswak. Medical history, intraoral examination followed by full mouth scaling was done. Gingival index (GI) and Plaque Index (PI) was recorded at baseline; visit I after 02 weeks and visit II after 06 weeks and then evaluation was made. Data was analyzed by SPSS version-21. Results: Overall 60 subjects were studied; 50% of them were tooth brush users and 50% were miswak users. The mean age of the both tooth brush and miswak user groups were 24.4±5.5 and 28.4±4.8 years, respectively. Of 30 users of the tooth brush; males were 20 and females were 10; whereas out of 30 miswak users, males were 25 and females were only 5. During follow-up visits, miswak and toothbrush user groups revealed showed no significant variances when compared according to GI and PI index. Findings revealed that in the removal of plaque, the use of both the miswak and the toothbrush is similarly effective whereas the toothbrush is even better than miswak in enhancing the gingivitis. Conclusion: Miswak and the toothbrush were equally effective. The use of miswak is somewhat more effective in removing dental plaque and tooth brush in improving gingivitis.